Clinical characteristics and medical therapy in randomized clinical trial eligible-and-enrolled vs. eligible-but-not enrolled patients with ischaemic heart failure. (14th October 2021) - Czyz, L; Chmiel, J; Mazurek, A; Drabik, L; Kwiecien, E; Sikorska, M; Skubera, M; Kozynacka, A; Olszowska, M; Zasada, W; Podolec, P; Musialek, P
Abstract: Introduction: Clinical trial applicability to routine clinical practice is a fundamental consideration. Little is known about eligibility and enrolment in ischaemic heart failure (iHF) trials. Aim: To compare clinical characteristics and medical therapy between subjects eligible-and-enrolled vs eligible-but-not-enrolled in iHF interventional randomized controlled trials (RCT). Material and methods: Using our detailed database of consecutive hospitalizations, iHF patients clinical characteristics and medical treatment were compared for 4 following periods: P1 (6 months of RCT#1 recruitment), P2 (6 months after the RCT#1), P3 (6 months of RCT#2 recruitment), P4 (6 months after RCT#2). RCT#1 and RCT#2 had similar criteria that involved 18–80 years old, NYHA Class II-IV inclusion and LVEF ≤40% (inclusion), and tumor/neoplasm history, recent (≤3 months) or planned major surgery, heart transplant waiting list (exclusion). Eligibility and enrolment, and reasons for non-eligibility and non-enrolment, were evaluated along baseline clinical characteristics and medical treatment. Results: Data of 5, 436 patients were reviewed. Eligibility rate was similar between the periods evaluated (P1–56.45%, P2–43.14%, P3–58.49%, P4–50.25%). One in 2 (50.62%) ineligible patients had a single-only reason for ineligibility (recent [≤3 months] or recommended cardiac surgery/cardiovascular intervention outside the trial 16.3%, age>80 years 14.6%, Fig. 1 and Fig. 2). 13.2% of eligible patients were not enrolled due to lack of consent. Eligible-and-enrolled patients did not differ in baseline clinical characteristics such as sex, age, diabetes, and the clinical stage of heart failure against the eligible-but-not-enrolled patients. However, the eligible-and-enrolled had lower left ventricle ejection fraction (echocardiography; 31.2% vs. 33.9%, p=0.0393) and higher end-diastolic volume (197.8ml vs 160.4ml, p<0.0001). There were no differences in ACE/ARB inhibitor, B-blocker, diuretic (thiazide, loop, K+ sparing), sacubitril/valsartan and statin therapy between the groups. Eligible patients characteristics were not different between the recruitment (P1, P3) and non-recruitment periods (P2, P4). Conclusion: Enrolment rate was high. Ineligibility resulted mainly from recent or recommended cardiovascular intervention outside RCT. Medical treatment was similar between eligible-and-enrolled and eligible-but-not-enrolled patients. Age (when within the inclusion criteria), gender and time frame were not factors of bias. However, the trial-enrolled patients had more severe left ventricle impairment. This argues, for iHF RCTs, against the routinely assumed lower-risk patient enrolment bias as signalled in other trial types and populations. FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): John Paul II Hospital, Krakow, Poland